-14-3x=-8x+9

Simple and best practice solution for -14-3x=-8x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -14-3x=-8x+9 equation:


Simplifying
-14 + -3x = -8x + 9

Reorder the terms:
-14 + -3x = 9 + -8x

Solving
-14 + -3x = 9 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-14 + -3x + 8x = 9 + -8x + 8x

Combine like terms: -3x + 8x = 5x
-14 + 5x = 9 + -8x + 8x

Combine like terms: -8x + 8x = 0
-14 + 5x = 9 + 0
-14 + 5x = 9

Add '14' to each side of the equation.
-14 + 14 + 5x = 9 + 14

Combine like terms: -14 + 14 = 0
0 + 5x = 9 + 14
5x = 9 + 14

Combine like terms: 9 + 14 = 23
5x = 23

Divide each side by '5'.
x = 4.6

Simplifying
x = 4.6

See similar equations:

| x/4+4/7=7/8 | | 30X=0.8 | | 1.8x-7.2=1.8 | | 8u-8=0 | | f(t)=-13t^2+14t+1 | | 180-2x/2 | | 9w-18=0 | | ln(-3x-10)-ln(10)=3 | | -10=-6y-17 | | 2x+(90-x)+(90-x)=180 | | 36x^3-108x=0 | | -4(x+2)+4=6(x+4)+3 | | 16=-3y+1 | | (5x+1)-(-2x+7)= | | -1=-4z-19 | | -5x-7y=24 | | f(x)=5x^2-9x | | -7x^3+3x^3= | | x-.6x-.17=.33x-.27 | | -8x^2+7+9x^2-12-5x= | | 1244=0.083x+0.076(3x) | | y-(-4)=9/4(x-(-7)) | | 5x^2-11x+3-6x-13x^2= | | 16+22p=0.8986 | | 5+5p-(5p+7)-(3p+9)= | | 8x^2+3x-5-12x^2= | | 35=2x-10 | | -4xw+x-xw+6x= | | -2(2y+3)-y= | | 1.5(0.16)=0.24 | | 30t^2+t-31=0 | | -(-2v-y)+(-4y+4v)= |

Equations solver categories